2017
DOI: 10.1248/cpb.c16-00993
|View full text |Cite
|
Sign up to set email alerts
|

Formulation Optimization of Gastro-Retention Tablets of Paeonol and Efficacy in Treatment of Experimental Gastric Ulcer

Abstract: This study aims to develop a gastroretentive sustained-release drug delivery system of paeonol using floating properties and to investigate its therapeutic effects in rat models. The gastric retention tablets of paeonol (GRT-Ps) were prepared by a direct compression method, and the Box-Behnken design was used to optimize its formulation. The optimized formulation containing 15% NaHCO 3 and a 2 : 1 ratio of paeonol and HPMC-K4M floated within 1 min and remained afloat for more than 8 h in the simulated gastric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…The present study revealed gastroprotective influence of paeonol at both low and high doses that was mediated through its antioxidant, anti-inflammatory, and antiapoptotic effects. Paeonol ability to reduce the ulcer index was comparable to the reference drug, ranitidine, and in accordance with the gastroprotection reported by Zhang et al 13 Oxidative damage observed in the gastric mucosa of IND group was well explained by Maity et al 29 Paeonol ameliorated IND-induced lipid peroxidation in the gastric mucosa may be owed to its previously reported antioxidant property. 10,11,13 The current study shows that paeonol replenished GSH content, restored SOD activity, and increased HO-1 gene expression in the gastric mucosa.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The present study revealed gastroprotective influence of paeonol at both low and high doses that was mediated through its antioxidant, anti-inflammatory, and antiapoptotic effects. Paeonol ability to reduce the ulcer index was comparable to the reference drug, ranitidine, and in accordance with the gastroprotection reported by Zhang et al 13 Oxidative damage observed in the gastric mucosa of IND group was well explained by Maity et al 29 Paeonol ameliorated IND-induced lipid peroxidation in the gastric mucosa may be owed to its previously reported antioxidant property. 10,11,13 The current study shows that paeonol replenished GSH content, restored SOD activity, and increased HO-1 gene expression in the gastric mucosa.…”
Section: Discussionsupporting
confidence: 86%
“…9 These properties of paeonol offered the basis for its function as an organ protective agent in various disease models. [10][11][12] Despite that the role of paeonol in the gastrointestinal diseases was examined, 13 the mechanisms underlying its gastroprotective effect need to be clarified. The present study aimed at elucidating possible mechanisms underlying paeonol protective effect on gastric ulcer.…”
Section: Introductionmentioning
confidence: 99%